Russian Federation : Targeted Detailed Assessment of Observance of Basel Core Principles for Effective Banking Supervision. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This paper focuses on targeted detailed assessment of observance of the Basel Core Principles for effective banking supervision. The selection of the principles to be reassessed was made by the mission team based on an analysis of the risks and vulnerabilities of the Russian Federation. It was revealed that the Central Bank of Russia (CBR) Law does not establish requirements for banks to seek prior CBR approval when making domestic investments in nonbank financial institutions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet